P‐13.2: Optimizing Pad Bending Structure Based on Numerical Simulation to Prevent Metal Line Crack. (26th August 2021) - Zhou, Min; Liu, Yifei; Huang, Rong; Cao, Weiran; Jing, Xiaohong; Hwang, Jason
Abstract : This article applied numerical simulation to prevent metal line crack failure under extreme pad bending radius like 0.35mm. In this study, the relationship between the metal stress and various thickness designs of pad bending layers such as UV Glue, Bank & PLN, ODH and PI was investigated. Furthermore, the effect of the neutral layer shift would be studied as well. The simulation result shows that either thinner UV or thicker ODH lowers the metal stress efficiently. However, PI shows an irregular relationship with the metal stress, and the influence of the bank thickness is not such obvious as others. After the layers thickness optimization, compared with the original design, metal stress in the optimized structure has been reduced by 67.21%, and the neutral layer gets closer to the metal line ( from 10.97μm to 0.62μm), which explains metal stress reduction.